Aerobic Training Increases Hippocampal Volume and Protects Cognitive Function for Type 2 Diabetes Patients with Normal Cognition - Wang, Ying; Wang, Liping; Yan, Juan; Yuan, Xiaodan; Lou, Qing Q. (Experimental and Clinical Endocrinology & Diabetes, 2023)
Aim To evaluate the effects of aerobic training on hippocampal volume and cognitive function in patients with type 2 diabetes mellitus (T2DM) with normal cognition.Materials and methods One hundred patients with T2DM aged 60–75 years who met inclusion criteria were randomized into the aerobic training group (n=50) and control group (n=50). The aerobic training group received 1 year of aerobic training, while the control group maintained their lifestyle without additional exercise intervention. The primary outcomes were hippocampal volume measured by MRI and Mini-mental State Examination (MMSE) score or Montreal Cognitive Assessment scale (MoCA) scores.Results Eighty-two participants completed the study (aerobic training group, n=40; control group, n=42). There was no significant difference between the two groups at baseline (P>0.05). After one year of moderate aerobic training, increase in total and right hippocampal volume in the aerobic training group were significantly higher than in the control group (P=0.027, P=0.043, respectively). In the aerobic group, total hippocampal volume significantly increased after the intervention compared with baseline (P=0.034). The between-group difference in the change of MMSE and MoCA scores was statistically significant (P=0.015, P=0.027, respectively). Logistic regression showed strong correlations between aerobic training and increase in total hippocampal volume (OR:1.091, [95%CI 0.969, 1.228], P=0.002), improvement of MMSE scores (OR:1.127, [95%CI 1.005, 1.263], P=0.041) or MoCA scores (OR:2.564, [95%CI 2.098.2.973], P=0.045).Conclusions One-year moderate aerobic training increased total and right hippocampal volume and protected cognitive function for T2DM patients with normal cognition. Early intervention focusing on cognition protection should be considered for T2DM patients in clinical settings.
Keywords: aerobic training; hippocampal volume; cognitive function; type 2 diabetes